2021
DOI: 10.3389/fimmu.2021.638444
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Adalimumab Biosimilars: Current Critical Clinical Data in Rheumatoid Arthritis

Abstract: Adalimumab, as a TNF inhibitor biologic for the treatment of rheumatoid arthritis, is one of the top-selling drugs worldwide. As its various patents have gradually expired, experiments on its biosimilars are constantly being implemented. In this review, we summarized clinical trials of seven biosimilars currently approved by the FDA and/or EMA for the treatment of rheumatoid arthritis, namely: ABP 501 (Amjevita/Amgevita/Solymbic), BI 695501 (Cyltezo), SB5 (Imraldi/Hadlima), GP2017 (Hyrimoz/Hefiya/Halimatoz), M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…RA often requires treatment with anti-inflammatory drugs that may affect the correlation between RA and risk of PD. Drugs commonly used in RA patients are non-steroidal anti-inflammatory drugs (NSAIDs) and immunosuppressive drugs including traditional disease-modifying anti-rheumatic drugs (DMARDs) (such as methotrexate, hydroxychloroquine, cyclosporine, azathioprine, and leflunomide) and biologic DMARDs (such as adalimumab, rituximab, etanercept, abatacept, golimumab, and tocilizumab) ( 27 , 28 ). Some epidemiological studies have suggested that NSAIDs may be protective against the development of PD ( 29 , 30 ), and basic experiments also showed that NSAIDs could reduce the formation of neurotoxic molecules and inhibit dopaminergic neurotoxicity, thereby exerting neuroprotective effects ( 31 – 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…RA often requires treatment with anti-inflammatory drugs that may affect the correlation between RA and risk of PD. Drugs commonly used in RA patients are non-steroidal anti-inflammatory drugs (NSAIDs) and immunosuppressive drugs including traditional disease-modifying anti-rheumatic drugs (DMARDs) (such as methotrexate, hydroxychloroquine, cyclosporine, azathioprine, and leflunomide) and biologic DMARDs (such as adalimumab, rituximab, etanercept, abatacept, golimumab, and tocilizumab) ( 27 , 28 ). Some epidemiological studies have suggested that NSAIDs may be protective against the development of PD ( 29 , 30 ), and basic experiments also showed that NSAIDs could reduce the formation of neurotoxic molecules and inhibit dopaminergic neurotoxicity, thereby exerting neuroprotective effects ( 31 – 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is an anti-TNF-α monoclonal antibody approved by Food and Drug Administration (FDA) and European Medicines Agency (EMA) for the treatment of rheumatoid arthritis, juvenile idiopathic arthritis, psoriatic arthritis, ankylosing spondylitis, Crohn's disease, plaque psoriasis, and hidradenitis suppurativa [13]. Its rare side effects include worsening or initiation of congestive heart failure, lupus-like syndrome, lymphoma, cytopenias, worsening or initiation of multiple sclerosis/neurological diseases, pancytopenia, and increased liver transaminases [14].…”
Section: Adalimumabmentioning
confidence: 99%
“…The tumor necrosis factor (TNF) inhibitor adalimumab (ADA) was the first fully human monoclonal antibody approved for use in RA (AbbVie Inc., Humira ®, Europe, 2003 [ 6 ], USA, 200 [ 7 ]). Since the originator product patent expired in 2016 (USA; Europe, 2018) [ 8 ], seven ADA biosimilars have been approved for use in RA [ 9 , 10 ]. Biosimilars are biotherapeutic products that are highly similar in pharmacokinetic, safety, immunogenic, and efficacy profiles to the licensed biotherapeutic reference product (bio-originator), and could reduce the treatment cost, thereby improving access to optimal therapy [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Switching trials have shown that switching from the ADA bio-originator to a currently approved biosimilar does not significantly impact safety, immunogenicity, or efficacy [ 10 ]. Subtle differences were considered to be due to methodological differences rather than the biosimilar properties [ 10 ].…”
Section: Introductionmentioning
confidence: 99%